Long-term seasonal changes in the abundance of Dendrodoris nudibranchs: a five-year survey - Cyrne, Ricardo Sousa (2015)
Researchers' interest in nudibranch species has grown during the last decades mainly due to their potential in biotechnology and neurobiology. However, a low number of ecological studies have been undertaken on this mollusk group, especially using long-term scales. In certain intertidal and subtidal locations some species of nudibranchs suddenly appear in very large numbers and also suddenly disappear. These seasonal events are observed and explained by several theories, being the most accepted the migration theory – inshore movements to copulate and egg deposition. However, controversy still exists in whether nudibranchs migrate or not. The aim of the present thesis is to study the migration behavior towards the intertidal zone of two nudibranch species, Dendrodoris herytra and D. grandiflora in Sado estuary, Portugal. Here it is shown that Dendrodoris nudibranchs start to appear in the intertidal areas in March and completely disappear around July, reaching pick density between April and May. Possible connections between Dendrodoris migrations with environmental parameters such as salinity, water and air temperature and water turbidity were assessed. The latter environmental factor revealed the strongest association with nudibranchs’ presence in such intertidal areas; i.e. the peak in nudibranch density was consistently observed during the period of higher turbidity. Since most of the individuals were mature and ready to spawn when caught, one may argue that the increased turbidity (as a proxy of increased phytoplankton biomass) should directly enhance the survival rate of planktotrophic larvae. Other possible explanations may include food foraging, as well as predator avoidance. During this long therm survey of five years, the density of emmerged individuals was very consistent. The environmental factors gave clues on what triggers this seasonal events, and how they induce the periodic appearance during spring months. The fact that both species were observed emmerged during low tide increases even more the interest in them and their biology. Nevertheless the great contribution of this research to nudibranchs ecology, studies still need to be undertaken to fully understand the causes behind the occurrence of such episodic events.